Empirical Analysis on Investor Protection in Minimizing Fraud Risk From Investment Managers - Retnowati, May Shinta; puspitasari, Intan; Kamila , Arfah (Universitas Darussalam Gontor, 2024)
**English**Violations related to the capital market are special criminal acts as shown by various types of violations. These violators can be committed by various parties including directors, commissioners, and other manager-level officials; professionals such as brokers, investment advisors, accountants, lawyers, and appraisers; and issuers or public companies that are affected themselves. Such as violations committed by investment managers that give rise to investment risks felt by investors, such as Providing false information that deceives investors In order to maintain the stability of activities in the capital market, it is necessary to have Legal protection can be defined as actions that seek to prevent and punish and provide sanctions. In this study, a literature method with an empirical studies approach is used. The results of this study show that there are various forms of protection for actors in the capital market. By safeguarding their investments, the Investor Protection Fund (DPP) provides confidence and security to investors when they are involved in the capital market. According to Article 110 paragraph (1) of the Capital Market Law, market violations include operations carried out without OJK permission, investment managers who receive money illegally, and attempts to thwart OJK inspections. because in the capital market, the role of the OJK carries out its 3 functions, namely rule making, adjudicatory, and investigatory to support its responsibilities so that it is carried out properly For violations and crimes in the capital market, the Capital Market Law applies three types of sanctions, there are civil sanction, criminal sanction, and witness administrative. **Indonesia**Pelanggaran yang terkait dengan pasar modal merupakan tindak pidana khusus yang ditunjukkan dengan berbagai jenis pelanggaran. Pelanggar ini dapat dilakukan oleh berbagai pihak termasuk direksi, komisaris, dan pejabat setingkat manajer lainnya; profesional seperti broker, penasihat investasi, akuntan, pengacara, dan penilai; dan emiten atau perusahaan publik yang terkena dampaknya sendiri. Seperti pelanggaran yang dilakukan oleh manajer investasi yang menimbulkan risiko investasi yang dirasakan oleh investor, seperti Memberikan informasi palsu yang menipu investor Dalam rangka menjaga stabilitas kegiatan di pasar modal, perlu memiliki Perlindungan hukum dapat didefinisikan sebagai tindakan yang berusaha mencegah dan menghukum serta memberikan sanksi. Dalam penelitian ini digunakan metode literatur dengan pendekatan studi empiris. Hasil penelitian ini menunjukkan bahwa terdapat berbagai bentuk perlindungan bagi pelaku di pasar modal. Dengan menjaga investasinya, Dana Perlindungan Investor (DPP) memberikan kepercayaan dan keamanan kepada investor ketika mereka terlibat di pasar modal. Menurut Pasal 110 ayat (1) UU Pasar Modal, pelanggaran pasar meliputi operasi yang dilakukan tanpa izin OJK, manajer investasi yang menerima uang secara ilegal, dan upaya menggagalkan pemeriksaan OJK. karena di pasar modal, peran OJK menjalankan 3 fungsinya, yaitu pembuatan peraturan, ajudikasi, dan penyidikan untuk mendukung tanggung jawabnya agar terlaksana dengan baik Untuk pelanggaran dan kejahatan di pasar modal, UU Pasar Modal menerapkan tiga jenis sanksi, ada sanksi perdata, sanksi pidana, dan saksi administratif.